2009
DOI: 10.1177/0018720809337716
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Control During Simulated Driving With a Concurrent Verbal Working Memory Task

Abstract: Because of the demonstrated differences in sensitivity and diagnosticity, researchers should consider the use of cardiac measures in addition to driving performance measures when studying attention in a driving simulator environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 43 publications
5
57
0
Order By: Relevance
“…It is not our intent to argue that any particular physiological measure of workload is inherently superior to another. While heart rate provided the most robust measure here, there are limited but known situations in which heart rate can be expected to remain low or even drop under conditions of hightened arousal (Lenneman & Backs, 2009;Mehler, Reimer, Pohlmeyer & Coughlin, 2008). We believe that data presented provide additional evidence for the position that various measures have varying utility depending on the conditions underwhich testing is taking place and the nature of the workload that is being assessed; multiple measures are certainly to be valued in research contexts such as combining heart rate and skin conductance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not our intent to argue that any particular physiological measure of workload is inherently superior to another. While heart rate provided the most robust measure here, there are limited but known situations in which heart rate can be expected to remain low or even drop under conditions of hightened arousal (Lenneman & Backs, 2009;Mehler, Reimer, Pohlmeyer & Coughlin, 2008). We believe that data presented provide additional evidence for the position that various measures have varying utility depending on the conditions underwhich testing is taking place and the nature of the workload that is being assessed; multiple measures are certainly to be valued in research contexts such as combining heart rate and skin conductance.…”
Section: Discussionmentioning
confidence: 99%
“…While much of this work was initially carried out in aviation (Kramer, 1991;Roscoe, 1992;Veltman & Gillard, 1998), a substantive literature is emerging using physiological measures such as heart rate in driving related research as well (Brookhuis & de Waard, 2001;Collet, Clarion, Morel, Chapon & Petit, 2009;Lenneman & Backs, 2009;Wilson, 2002). In addition to basic heart rate, there has also been growing interest in various measures of heart rate variability (HRV).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a number of studies have shown that simulated driving in which velocity is fixed (primarily a perceptual/motor processing task) elicits only a decrease in HRV. [9,10] Further, Lenneman & Backs [10] were able to show that adding a verbal working memory task (primarily a perceptual/central processing task) to simulated driving (primarily a perceptual/motor processing task) elicits a decrease in PEP and HF-HRV. They were also able to demonstrate that cardiac measures can differentiate between performance on the 0-back item recognition task and the 3-back working memory task.…”
Section: Enhancing Diagnosticity Through Use Of Cardiac Measuresmentioning
confidence: 98%
“…[7,8] In our lab, we have repeatedly shown that demands of a side-task can elicit significant cardiac responses with no effect on driving performance. [9,10,11] In Lenneman and Backs [10], subjects were asked to concurrently perform a simulated driving task and a verbal working memory task. While driving, subjects had to maintain their position in the center of the lane and also perform an n-back letter recall task (the subject had to decide if the current letter presented matches the nth letter previously presented).…”
Section: Enhancing Sensitivity Through Use Of Cardiac Measuresmentioning
confidence: 99%
“…Research suggests that physiological indices of workload reflect an individual's investment of cognitive resources corresponding to task demand (Brookhuis & de Waard, 1993;Lenneman & Backs, 2009;Mehler, Reimer, Coughlin, & Dusek, 2009;Mehler, Reimer & Coughlin, 2012;Wilson, 2002). Physiological measures have been shown to be sensitive to subtle increases in demand prior to overt breakdowns in driving performance are observed (Mehler, Reimer, Coughlin, & Dusek, 2009).…”
Section: Introductionmentioning
confidence: 99%